2019
DOI: 10.3390/en12122262
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the MgO-CO2 Working Pair for Thermochemical Energy Storage by Doping with Salts: Effect of the (LiK)NO3 Content

Abstract: The MgO-CO2 working pair has been regarded as prospective for thermochemical energy storage (TCES) due to its relatively high heat storage capacity, low cost, and wide availability. This study is aimed at the optimization of the molar salt content, α, for the MgO modified with the eutectic mixture of LiNO3 and KNO3 (Li0.42K0.58NO3) which was earlier shown to provide high conversion, Δx, in heat-storage/release processes at 300–400 °C. The composites that have different salt content were prepared and carbonatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…By reversible carbonation−regeneration operations, the MgCO 3 /MgO system promoted with Li 0.42 K 0.58 NO 3 binary salts is capable of harvesting 1600 kJ/ kg thermal energy from ∼330 °C waste heat. 29,30 When the carbonation process is operated at 340 °C in 100% CO 2 , the desired 10(Li−Na)NO 3 −MgO composite in this work demonstrates outstanding TCES performance with a high heat storage density of 1702 kJ/kg. The heat storage For the composites such as MgCeLi-4-3, MH/CTAB 2.0, and Li 0.42 K 0.58 NO 3 /MgO, their average heat storage rates are in the range of 5.17−7.86 kJ/(kg•min).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…By reversible carbonation−regeneration operations, the MgCO 3 /MgO system promoted with Li 0.42 K 0.58 NO 3 binary salts is capable of harvesting 1600 kJ/ kg thermal energy from ∼330 °C waste heat. 29,30 When the carbonation process is operated at 340 °C in 100% CO 2 , the desired 10(Li−Na)NO 3 −MgO composite in this work demonstrates outstanding TCES performance with a high heat storage density of 1702 kJ/kg. The heat storage For the composites such as MgCeLi-4-3, MH/CTAB 2.0, and Li 0.42 K 0.58 NO 3 /MgO, their average heat storage rates are in the range of 5.17−7.86 kJ/(kg•min).…”
Section: Resultsmentioning
confidence: 93%
“…The backward carbonation allows the heat to be released and reused whenever needed (discharging). 29,30 As a result, the energy storage efficiency depends on the carbonation conversion. Among various alkali/ alkaline metal-based materials, MgO shows the highest theoretical CO 2 storage capacity of 1.1 g CO 2 /g adsorbent.…”
Section: Mgco (S)mentioning
confidence: 99%
“…The lithium salts used as dopants are listed in Table 2. As can be seen in the table, the main doping lithium-based salts are LiCl [63,64], LiOH [61,64], LiNO3 [65,66], Li4SiO4 [67] and LiKNO3 [62,68]. These salts have been used in multiple investigations, showing good thermal stability and expanding the applicability of the compounds as a heat storage materials.…”
Section: Lithium In Tcs Chemical Reactionsmentioning
confidence: 99%
“…The work demonstrated that the de-carbonation process can be carried out at T > 330 °C, and that the heat storage capacity of the doped salt MgO was estimated to be 1600 kJ/L, concluding that these parameters are promising for TCS (Figure 10). In the same way, Kim et al [68] adapted the MgO/CO2 working pair to study the effect of doping with (LiK)NO3. To do this, a number of carbonation dynamic experiments were carried out.…”
Section: Lithium In Tcs Chemical Reactionsmentioning
confidence: 99%
“…To date, most works on TCS have been focused on fundamental studies on the reactive materials, including their stability and cyclability under the operating conditions of the storage systems, and their intrinsic storage capacity. Particularly the attention has been focused on oxides (principally manganese [4] and cobalt [5], and more recently others like ceria based oxides [6]), hydroxides (mainly calcium [7] and magnesium [8] based hydroxide), and carbonates (calcium [9,10] and magnesium [11] based carbonates), from fundamental chemical development and characterization [12] to the analysis and testing at the component level [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%